AN EXPRESSION OF DIFFERENT GENERATIONS IN AN ORGANIZATION: A SYSTEMATIC LITERATURE REVIEW - Statnickė, Gita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The concept of generation is examined in many sciences such as sociology, philosophy, pedagogy, anthropology, biology, history, management, etc. Generation as a construct is intricate, and researchers from various fields have tried to define this extraordinary phenomenon. The aging population representatives of different generations live longer, so the differences between generations are becoming increasingly noticeable. This article examines the concept of generation, analyses the main theories of generations and presents a theoretical approach to a generational expression in an organization. The aim of the research is to reveal a theoretical approach to the expression of different generations in an organization, i.e. to analyse studies related to the expression of different generations in an organization and to identify the main research fields related to the subject. The primary method used in the article is a systematic literature review (SLR). The systematic literature review (SLR) disclosed that although the topic of expression of different generations in an organization is relevant among the human resources management (HRM) specialists-practitioners, nevertheless, there is a lack of high-level publications in Europe containing empirical research on this subject, i.e. there is a lack of a systematic scientific approach to this topic, and therefore, this area is under-researched.